2020
DOI: 10.1002/anie.201915547
|View full text |Cite
|
Sign up to set email alerts
|

Nitrenium Salts in Lewis Acid Catalysis

Abstract: Molecular compounds featuring nitrogen atoms are typically regarded as Lewis bases and are extensively employed as donor ligands in coordination chemistry or as nucleophiles in organic chemistry.B yc ontrast, electrophilic nitrogencontaining compounds are muchr arer.N itrenium cations are an ew family of nitrogen-based Lewis acids,t he reactivity of which remains largely unexplored. In this work, nitrenium ions are explored as catalysts in five organic transformations.These reactions are the first examples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 55 publications
0
45
0
1
Order By: Relevance
“…elegantly demonstrated that the naphthotriazinium cation can serve as a Lewis acid catalyst in several organic reactions (Scheme 1 c). [14] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…elegantly demonstrated that the naphthotriazinium cation can serve as a Lewis acid catalyst in several organic reactions (Scheme 1 c). [14] …”
Section: Methodsmentioning
confidence: 99%
“…Recently, Goicoechea et al elegantly demonstrated that the naphthotriazinium cation can serve as a Lewis acid catalyst in several organic reactions (Scheme 1 c). [14] Herein, we report on our synthesis of a new, Lewis acidic NHN cation, which is capable of cleaving Si À H bonds in silanes, when combined with a suitable Lewis base. To the best of our knowledge, it is the first example of a FLP consisting of a N-based Lewis acid, capable of cleaving an electrophilehydride (EÀH) type bond, which is relevant to numerous catalytic processes.…”
mentioning
confidence: 99%
“…Gandelman and co-workers have also expanded the range of triazolium salts, demonstrating access to aw ide variety of N-based Lewis acids. [24][25][26][27] More recently,M ehta and Goicoechia [28] as well as Gandelman [29] have exploited the Lewis acidity of triazinium salts for Lewis acid catalysis and FLP SiÀHa ctivation.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Recently, group 14 and group 15 LAs were introduced in FLP chemistry including tetrylium [27][28][29][30][31][32][33] and phosphonium LAs. [34][35][36][37][38][39][40][41][42][43][44] Cationic tetrylium LAs were used with amines to effect H2 activation. Especially Stannyliums were demonstrated as promising FLP LAs due to their excellent moisture tolerance leading to efficient catalytic hydrogenation protocols with a wide range of substrate scope.…”
Section: Introductionmentioning
confidence: 99%